BREKSI BATU APUNG SEBAGAI ALTERNATIF TEKNOLOGI TEPAT GUNA UNTUK MENURUNKAN KADAR TSS DAN BOD DALAM LIMBAH CAIR DOMESTIK - Triatmi Sri Widyaningsih (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2016)
Water is a vital necessity for life because without water, human and other creatures can not survive. Until now, Bu Anik’s restaurant in district Klaten has not had a system of domestic waste water treatment unit. Water pollution by waste water restaurant caused a decline in water quality in water bodies and groundwater, it is because liquid waste restaurant have a lot of organic matter. Based on this background, the research conducted to reduce waste water containing organic material by using pumice breccia as the main media. Studies using a PVC pipe 2 ½ inch amounted to four tubes with a length of 70 cm, one tube as a control while three other tubes filled with pumice breccia’s diameter is 8 mesh. Independent variable in this research that the media height between 20 to 70 cm. Pumice breccia is one of the absorbent which has binding properties of the molecules in the liquid surface. Before use pumice breccia, destroy first, in order to obtain a grain diameter of 8 mesh, washed, drying up and then hated in an oven at 200 o C for 2 hours, so that the liquid is trapped in rock can evaporate and then gives the pumice breccia’s absorption is more optimal.The result after treatment showed that the effect of the decreased levels of TSS and BOD in water samples. Average decline in media height 70 cm, from the initial sample concentration of 219.5 mg/L can drop to 85.46 mg/L (decrease efficiency 59.31 %) and for BOD at media height 60 cm, from the initial concentration 325.30 mg/L is able to drop to 63.52 mg/L (decrease efficiency 80.84%).